2013
DOI: 10.1111/nmo.12177
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic response to a visceral stressor is dysregulated in irritable bowel syndrome and correlates with duration of disease

Abstract: Background Previous studies reported altered autonomic nervous system (ANS) responses in IBS at baseline and to colonic balloon distension. This study examined heart rate variability (HRV) and plasma catecholamines as an index of ANS responsiveness in IBS during flexible sigmoidoscopy (FS) and explored associations of HRV with clinical measures. Methods Rome III positive IBS patients and healthy controls completed questionnaires measuring GI and psychological symptoms. HRV measures were calculated using elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 47 publications
(93 reference statements)
3
30
0
Order By: Relevance
“…In normal healthy subjects, rectal distention induces an increase in heart rate, and the low frequency/high frequency ratio of heart rate variability is used as a marker of cardiac sympathetic activity with a concomitant increase in rCBF in the right anterior insula [74]. On the other hand, IBS patients exhibit an impaired cardiac sympathetic and vagal response to colonic stimulation in response to flexible sigmoidoscopy [11]. These findings suggest that robust sympathetic arousal is a normal feature of the cardiac autonomic response to colorectal distention and that IBS patients have an abnormal autonomic response to painful stimuli to the colorectum.…”
Section: Stress and Visceral Painmentioning
confidence: 99%
“…In normal healthy subjects, rectal distention induces an increase in heart rate, and the low frequency/high frequency ratio of heart rate variability is used as a marker of cardiac sympathetic activity with a concomitant increase in rCBF in the right anterior insula [74]. On the other hand, IBS patients exhibit an impaired cardiac sympathetic and vagal response to colonic stimulation in response to flexible sigmoidoscopy [11]. These findings suggest that robust sympathetic arousal is a normal feature of the cardiac autonomic response to colorectal distention and that IBS patients have an abnormal autonomic response to painful stimuli to the colorectum.…”
Section: Stress and Visceral Painmentioning
confidence: 99%
“…It has been reported that IBS patients had significantly less cardiosympathetic and cardiovagal responsiveness after controlling age effect during flexible sigmoidoscopy which may cause visceral nociception. 28 The altered responses in the emotional-arousal network during visceral stimulation were shown in IBS patients by means of brain imaging techniques. [37][38][39] These brain regions are closely related to stress responses which often induce cardiovascular activation.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 The variables were analyzed by the non-parametric Mann-Whitney U statistic and the Spearman rank correlation coefficient to account for non-normal distributions of some variables. Categorical data were analyzed with the c 2 test.…”
Section: Methodsmentioning
confidence: 99%
“…Most previous investigations of somatic hypersensitivity involved only a single stimulus method, and the conclusions were contradictory (Whitehead et al, 1990;Zighelboim et al, 1995). Whether autonomic cardiovascular dysfunction is involved in the pathological process of IBS is controversial (Elsenbruch and Orr, 2001;Tousignant-Laflamme et al, 2006;Cheng et al, 2013). Finally, a growing body of research evidence suggests that damage to the intestinal mucosal barrier and low-grade inflammation of the gut wall are related to the pathogenesis of IBS (Peuhkuri et al, 2010;Snoek et al, 2010;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%